Addressing cancer treatment in an African setting: a bioinformatics analysis of pharmacogemically relevant varients - Da Rocha, Jorge (My University, 2018)
Cancer is a critical health burden in Africa, and mortality rates are rising rapidly. Treatments are severe and expensive, and often cause adverse-drug-reactions (ADRs). These may be attributed to variants in genes that encode proteins involved in key drug pathways. Most pharmacogenomics (PGx) research has been done in populations of European, Asian and African-American ancestry, with sparse data from African populations. Thirteen genes linked with ADRs to medicines used for treating major cancer types were identified: ABCB1, DPYD, TYMS, CYP19A1, GSTP1, CYP1B1, CYP3A4, CYP3A5, ESR1, CYP2D6, SLC19A1 and XRCC1/5. Public domain wholegenome-sequencing data from the 1000 Genomes Project and the African Genome Variation Project were mined to assess eight African populations. Functional annotation was performed with a series of bioinformatics-based scoring tools to assess potential likelihood of deleterious impact. Variants of high likelihood of deleterious impact, including some novel variants were identified. These novel variants, however, are rare and require further validation. Two key African specific variants were identified: the CYP3A5 frameshift variant, rs41303343, which is highly likely to knockout gene function, and the CYP2D6 missense variant rs59421388, which was scored highly likely deleterious by all tools. Both variants are common in Africans, at frequencies above 10%, but lack clinical investigation into their PGx impact. For missense variants with known PGx effects, such as CYP2D6 - rs1065852 and DPYD - rs2297595, African frequencies are significantly distinct from global populations (p < 1x10-4) (with rs1065852 less common, and rs2297595 more common in Africans respectively). There is also variation within Africa, with the rs1065852 A allele being more common in West Africans, while the rs2297595 C allele is more common in East Africans. These data indicate that guidelines for cancer drug safety based on African data is essential for use in Africa, and novel region-specific guidelines should be developed to ensure that Africans could benefit for a personalized medicine approach.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine, June 2018
Keywords: Neoplasms; Drug-Related Side Effects and Adverse Reactions